Strategies and customer satisfaction: A correlational study in a multi-brand automotive organization in Chiclayo - Salazar, Lorena Liseth Cubas; Lozada, Ricardo Zapata; Mejía, Percy Junior Castro (Edelweiss Applied Science and Technology, 2025)
In the research study, development skills and their correlation with user satisfaction were examined in a private multi-brand automotive organization in Chiclayo, with the objective of detecting the correlation of process course skills and compliance. Therefore, it was decided to resort to a basic correlational, non-experimental, cross-sectional, quantitative approach. The investigation focused on a private company, specifically its sales and after-sales divisions. The study was conducted in the warehouse area, involving 60 clients who purchased spare parts using sales receipts. We utilized a questionnaire as the tool and employed survey techniques. According to the conclusions obtained, it was determined that there is a considerable positive significant relationship (Rho=0.782) according to Spearman; therefore, the null hypothesis (H0) is rejected, and it is accepted that there is a relationship between the process strategies variables and the satisfaction of the clients of the private automotive company Interamericana Norte S.A.C - Chiclayo. Another important conclusion was regarding the information collected through the survey carried out with 20 questions asked; of the 53 clients surveyed, 37 are satisfied.